2020
DOI: 10.1016/j.apcatb.2020.119103
|View full text |Cite
|
Sign up to set email alerts
|

Controlled selectivity for ethanol steam reforming reaction over doped CeO2 surfaces: The role of gallium

Abstract: The ethanol steam reforming reaction, together with the adsorption and decomposition of ethanol was studied on CeO 2 and gallium-doped ceria (CeGaO x) by a combined experimental and theoretical approach using infrared spectroscopy (IR), mass spectrometry (MS) and density functional theory (DFT) calculations. At 100°C, different types of monodentate ethoxy species were identified as standing-up (SU) on Ce 4+ and lying-down (LD) on Ce 4+ and Ga 3+ , with the alkyl chain more perpendicular or parallel to the surf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 62 publications
(92 reference statements)
1
32
1
Order By: Relevance
“…Moreover, sodium promotes C-C scission. Ga doping of ceria-based catalysts improves the H 2 /CO 2 ratio in ESR reaction, by changing the product distribution and reducing the coke formation [48]. The stability of Co/CeO 2 and Ni/CeO 2 catalysts have been improved by the La 2 O 3 promoter, the carbon formation rate has been reduced as results of an increased active phase dispersion and a strengthening of the metal-support interactions [49].…”
Section: Ethanol Steam Reformingmentioning
confidence: 99%
“…Moreover, sodium promotes C-C scission. Ga doping of ceria-based catalysts improves the H 2 /CO 2 ratio in ESR reaction, by changing the product distribution and reducing the coke formation [48]. The stability of Co/CeO 2 and Ni/CeO 2 catalysts have been improved by the La 2 O 3 promoter, the carbon formation rate has been reduced as results of an increased active phase dispersion and a strengthening of the metal-support interactions [49].…”
Section: Ethanol Steam Reformingmentioning
confidence: 99%
“…To‐date, the wide band gap gallium oxide (Ga 2 O 3 ) has achieved considerable attraction, owing to its versatility as a passivation layer for AlGaN/GaN MOS high‐electron‐mobility transistors (HEMT), 8,9 Si solar cells, 10 InGaN light‐emitting diode, 11 solar‐blind ultraviolet detectors, 12 window layer for optoelectronic devices, and water splitting 13 . Literatures have reported the aspects of generating higher amount of oxygen vacancies in the doped CeO 2 as well as enhanced redox activities yet the findings with regard to high‐ k MOS application remains rare 14 . The wide band gap (4.4‐4.9 eV) and moderate k value (10) of Ga 2 O 3 8,9,15 coupled with CeO 2 are anticipated to yield a wider tunability in term of k and band gap, leading to the formation of Ga 3+ doped CeO 2 with improved MOS characteristics, which have not been explored thus far.…”
Section: Introductionmentioning
confidence: 99%
“…13 Literatures have reported the aspects of generating higher amount of oxygen vacancies in the doped CeO 2 as well as enhanced redox activities yet the findings with regard to high-k MOS application remains rare. 14 The wide band gap (4.4-4.9 eV) and moderate k value (10)…”
mentioning
confidence: 99%
“…The efforts of doping Ga 3+ into CeO 2 have been initiated, and findings divulged that the interaction of Ga with CeO 2 would weaken the Ce--O bonds, and thus providing a higher number of actives sites for enhancement of the catalytic behaviour. 20 Besides, the introduction of Ga 3+ to CeO 2 lattice would generate negative oxide charges, which would thus compensate for effective positive oxide charges commonly present in high k oxides. 33 Nonetheless, the details were not specified and the relevant investigation on employing Ga 3+ doped CeO 2 to passivate MOS devices is not present.…”
mentioning
confidence: 99%
“…To date, previous literature has reported the synthesis of bulk Ga x Ce y O z material for controlled selectivity over ethanol steam reforming reaction, 20 hydrogen purification for fuel cells, 23 and hydrogenation of acetylene. 34 The investigation of the Ga x Ce y O z material as a high k passivation layer is meagre and thus far, only one study was reported.…”
mentioning
confidence: 99%